UPAYA MENINGKATKAN HASIL BELAJAR BANGUN RUANG SISI LENGKUNG MELALUI PEMBELAJARAN KOOPERATIF BERMAKNA MENGGUNAKAN BENDA NYATA - Navianto, Andi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The purpose of this study was to describe efforts to improve learning outcomes of curved side shapes through meaningful cooperative learning using real objects in IX-A grade students of SMP Negeri 3 Pule in odd semesters of the 2018/2019 academic year. Class action research (CAR) was carried out in two cycles with each cycle consisting of three meetings. The stages of this research are planning, implementation of action, observation, and reflection. The research data collected is the result of observing student activities and student test results. The result showed an increase in student test result. In cycle I, the average student score was 57 with 25% classical mastery, increasing in cycle II to an average score of 87 with 83% classical completeness. From the increase in student test results, it can be concluded that the application of meaningful cooperative learning using real objects can improve learning outcomes for curved side shapes in IX-A grade students.